Thermal and Mechanical Properties of Ureaformaldehyde (UF) Resin Combined with Multiwalled Carbon Nanotubes (MWCNT) as Nanofiller and Fiberboards Prepared by UF-MWCNT - Gupta, Arun; Anuj, Kumar; Viswanathan Sharma , Korada (Walter de Gruyter GmbH, 2014)
The effect of multiwalled carbon nanotubes(MWCNT) as reinforcement on the properties of urea-formaldehyde (UF) resin and medium-density fiberboards was investigated. MWCNT was added to UF in two concentrations, and the effects were studied by means of differential scanning calorimetry and dynamic mechanical thermal analysis in terms of the curing and viscoelastic properties of the resins. In the presence of MWCNT, the activation energy of the resins was lowered, and their storage modulus and thermal conductivity were enhanced. The formaldehyde emission decreased and mechanical properties increased after addition of MWCNT to UF resin.